PENGARUH LITERASI KEWIRAUSAHAAN TERHADAP INTENSI BERWIRAUSAHA DENGAN KEINGINAN UNTUK BERPRESTASI DAN EFIKASI DIRI SEBAGAI VARIABEL MODERATOR - Dewi, Erni Sartika; Iskandar, Iskandar; Jumantini, Entin (Jurnal Pendidikan Ekonomi (JURKAMI), 2024)
The disparity between the number of graduates and the available job opportunities in Indonesia remains an issue. Despite the abundance of graduates, the job market cannot absorb them effectively. This study aims to determine the influence of entrepreneurial literacy, the desire for achievement, and self-efficacy on entrepreneurial intentions. It also examines the moderating effect of the desire for achievement on the relationship between entrepreneurial literacy and entrepreneurial intentions, as well as the moderating effect of self-efficacy on this relationship among 12th-grade vocational high school students in South Majalengka. This quantitative correlational study employs a survey method. The population comprises 1,074 12th-grade students from state vocational high schools in South Majalengka, with a sample size of 292. Data were collected using a questionnaire and analyzed through moderated regression. The findings indicate that entrepreneurial literacy significantly positively affects entrepreneurial intentions; the desire for achievement significantly positively influences entrepreneurial intentions; self-efficacy significantly positively impacts entrepreneurial intentions; the desire for achievement significantly strengthens the effect of entrepreneurial literacy on entrepreneurial intentions; and self-efficacy significantly reinforces the influence of entrepreneurial literacy on entrepreneurial intentions among these students. To enhance entrepreneurial intentions, intensive entrepreneurship training and facilitating active and collaborative learning for students can be undertaken.